2019
DOI: 10.1021/jacs.9b05952
|View full text |Cite
|
Sign up to set email alerts
|

Porphyrinic Silver Cluster Assembled Material for Simultaneous Capture and Photocatalysis of Mustard-Gas Simulant

Abstract: Silver cluster-assembled materials (SCAMs), by virtue of their tunable structure, accessible surface area and excellent stability, hold great promise as highly efficient catalysts. Herein, we report a new SCAM [Ag12(S t Bu)6(CF3COO)3(TPyP)] n (denoted as Ag12TPyP) composed of a Ag12 chalcogenolate cluster core stabilized by porphyrinic ligands. Ag12TPyP showed superior sulfur mustard simulant (2-chloroethyl ethyl sulfide, CEES) degradation efficiency and achieved a half lifetime (t 1/2) of 1.5 min with 100% s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
134
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(141 citation statements)
references
References 40 publications
(59 reference statements)
1
134
0
Order By: Relevance
“…entries 15,16). Additionally,t he turnover number (TON) study for this model reaction catalyzed by Ag27-MOF revealed the value is up to 1333, which is even higher than that for presently the most efficient heterogeneous catalyst TOS-Ag4 (930).…”
Section: Resultsmentioning
confidence: 81%
“…entries 15,16). Additionally,t he turnover number (TON) study for this model reaction catalyzed by Ag27-MOF revealed the value is up to 1333, which is even higher than that for presently the most efficient heterogeneous catalyst TOS-Ag4 (930).…”
Section: Resultsmentioning
confidence: 81%
“…It should be noted that a similar solvent-or gasmolecule-sensitive luminescence has been widely recorded in Ag(I) NC-based metal-organic frameworks (MOFs), which are usually bridged by N-containing heterocyclic cross-linkers. [219][220][221] The detection of large biomolecules (e.g., proteins) is another important topic in the sensor development of metal NCs. This detection largely depends on the specic bio-recognition and bio-conjugation interactions.…”
Section: Molecular Interactions/reactions In Sensing Applications Of mentioning
confidence: 99%
“…Recently, this group also formed a 2D CS with Ag 12 (S t Bu) 6 (CF 3 COO) 3 NCs as nodes by using 5,10,15,20-tetra(4-pyridyl)porphyrin (TPyP, Scheme 2 (11)) as a linker ( Figure 24 A) [ 171 ]. TPyP has a photosensitizing effect.…”
Section: Two-dimensional Structuresmentioning
confidence: 99%
“…( B ) Schematic illustration of the capture and photodetoxification of CEES by Ag 12 (S- t Bu) 6 (CF 3 COO) 3 (TPyP). Reproduced with permission from Reference [ 171 ]. Copyright 2019 American Chemical Society.…”
Section: Figures Schemes and Tablesmentioning
confidence: 99%